Exotic massive 3D gravities from truncation - Hamid Reza Afshar; Nihat Sadik Deger (Journal of High Energy Physics, 2019)
ABSTRACT We introduce a systematic way of constructing 3D exotic massive gravity theories in the first order formulation. Our method is based on truncating a single degree of freedom in the parity odd gravity models found earlier [1] and supplementing it with appropriate potential terms such that the resulting models have well-defined metric equations but their Bianchi identities are satisfied only on-shell. Hence, they are ‘third way’ consistent. We first re-derive two already known exotic theories using our approach and then construct an extended exotic massive gravity model whose metric field equation is sixth order in derivatives. We also explain how to check Bianchi identities using the first order formulation.